2022
DOI: 10.1002/mnfr.202101090
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Faecal Fermentation of Monomeric and Oligomeric Flavan‐3‐ols: Catabolic Pathways and Stoichiometry

Abstract: Scope The study evaluates the influence of flavan‐3‐ol structure on the production of phenolic catabolites, principally phenyl‐γ‐valerolactones (PVLs), and phenylvaleric acids (PVAs). Methods and Results A set of 12 monomeric flavan‐3‐ols and proanthocyanidins (degree of polymerization (DP) of 2–5), are fermented in vitro for 24 h using human faecal microbiota, and catabolism is analyzed by UHPLC‐ESI‐MS/MS. Up to 32 catabolites strictly related to microbial catabolism of parent compounds are detected. (+)‐Cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…with the mean cumulative urinary excretion of phenyl-γ-valerolactones (≈217 μmol) indicates that the ingestion of about 5 μmol of flavan-3-ols would potentially result in excretion of 1 μmol of phenyl-γ-valerolactones. This observation is in line with stoichiometry in the production of these C 5 -C 6 colonic metabolites from flavan-3-ol monomers and B-type dimers (Di Pede et al, 2022). Likewise, when comparing the mean cumulative urinary excretion of phenylvaleric acids (≈4 μmol)…”
Section: Methodsupporting
confidence: 81%
See 1 more Smart Citation
“…with the mean cumulative urinary excretion of phenyl-γ-valerolactones (≈217 μmol) indicates that the ingestion of about 5 μmol of flavan-3-ols would potentially result in excretion of 1 μmol of phenyl-γ-valerolactones. This observation is in line with stoichiometry in the production of these C 5 -C 6 colonic metabolites from flavan-3-ol monomers and B-type dimers (Di Pede et al, 2022). Likewise, when comparing the mean cumulative urinary excretion of phenylvaleric acids (≈4 μmol)…”
Section: Methodsupporting
confidence: 81%
“…These differences might be attributable to the high amount of flavan-3-ol monomers in cocoa (Sorrenti et al, 2020), more prone to gut microbiota metabolism (Crozier et al, 2010;Monagas et al, 2010;Borges et al, 2018;Di Pede et al, 2022). Indeed, the low number of metabolites recovered after berry intake was probably attributable to their richness in highly polymerized procyanidins (Nile and Park, 2014), which are less susceptible to catabolism by gut microbiota (Mena et al, 2015;Di Pede et al, 2022). On the other hand, it should be noted that when flavan-3-ols were consumed together with other flavonoids (i.e.…”
Section: Tablementioning
confidence: 99%
“…For example, transformation of 2-(phenyl)ethanol into phenylacetic acid by bacteria has been proven using human fecal samples, but the metabolizing species are yet to be pinpointed (Mosele et al, 2014). Using in vitro fermentation, Di Pede et al (2022) showed the resulting products of several proanthocyanins and flavan-3-ols along time, but the bacteria species responsible were not elucidated Likewise, even though the conversion of cinnamic acids into vinyl phenol has been reported across several bacteria and yeast species isolated from food, soil, and plants, the same was not found using human fecal samples (Mishra et al, 2014). It is possible that many of the alreadyidentified bacteria from gut microbiota produce many more LMW phenolic metabolites still to be identified.…”
Section: Gut Microbiota and The Lmw Phenolic Metabolitesmentioning
confidence: 99%
“…García-Villalba et al [11] provide a comprehensive review on the metabolism, associated gut microbiota, and bioactivity of urolithins, colonic metabolites derived from ellagitannins and ellagic acid. Di Pede et al [12] assess the influence of flavan-3-ol structure on the production of phenolic catabolites using an in vitro fecal fermentation model. Insights on the catabolic pathways of 12 monomeric flavan-3ols and procyanidins and the stoichiometry associated with the production of bioactive catabolites are provided.…”
mentioning
confidence: 99%
“…Di Pede et al. [ 12 ] assess the influence of flavan‐3‐ol structure on the production of phenolic catabolites using an in vitro fecal fermentation model. Insights on the catabolic pathways of 12 monomeric flavan‐3‐ols and procyanidins and the stoichiometry associated with the production of bioactive catabolites are provided.…”
mentioning
confidence: 99%